Geography teaching in early years:needs near childhood - Rudolf, Ana Paula; Martins, Rosa Elisabete Militz Wypyczynski (Revista Ensino de Geografia (Recife), 2020)
This paper aims to address the geography teaching to young children and is mostly focused on childhood aspects, their singularities, needs and rights. After mapping public policies such as LDB, DCNEB and BNCC, and reviewing relevant studies by Leite, (2012); Hess (2012); Costa (2016); Seferian (2018); Bonfim (2015); Rosa (2008), Martins (2010); Camacho (2015); Lopes (2008), Valladares (2015); Silva (2013), we gathered a few potentialities of teaching geography, by employing practices that bring children closer to the contents lived in their daily lives. Therefore, they can understand that geographyis around them, their home, school, neighborhood and city. By doing so, we aim to make geography teaching be more thoroughly understood and lived by children as a field enabling to interpret the world as a whole, and attributing a social and significant meaning to geography in the elementary school curriculum context